Pengaruh Media Sosial, Harga Dan Kualitas Produk Terhadap Minat Beli Generasi Z - Fadali Rahman; Mahrus Afandi; Moh Agung Wahyudi; Gilang Aditya Saputra; Dedy Andre Ansyah Zulkarnain; Adriani Kusuma (Jurnal Riset Multidisiplin Edukasi, 2025)
This study focused on examining the relationship between social media use, pricing, and product quality on Generation Z's purchasing intentions using the Systematic Literature Review (SLR) method. The review process was conducted by searching and filtering scientific articles published between 2020 and 2025 using the Google Scholar and Semantic Scholar databases. By applying the established inclusion criteria, ten articles were identified as relevant and met academic eligibility standards for analysis. Based on the literature synthesis results, social media-based marketing has generally been shown to contribute positively and significantly to increased purchasing intentions, although several studies have shown that this influence is not significant when tested partially. Findings related to the price variable show inconsistent results, ranging from a significant positive influence, to no significant influence, to a significant negative impact. This indicates that consumer perceptions of price are strongly influenced by the situation, preferences, and perceived value. Conversely, product quality emerged as the most consistent and dominant factor influencing purchasing intentions, indicated by a significant positive influence in almost all studies reviewed. Collectively, social media, price, and product quality have been shown to have a significant positive influence on consumer purchasing intentions. These findings confirm that effective marketing efforts need to integrate promotional strategies through social media, product quality improvements, and competitive pricing adjustments to attract Generation Z's purchasing interest in the digital era.